The construction of investor-subjects in a housing-led growth society: the case of Hong Kong - Gary Tang; Francis L. F. Lee; Chung-Kin Tsang (The Social Science Journal, 2026)

The potential of foodwaste leachate as a phycoremediation substrate for microalgal CO2 fixation and biodiesel production - Kam-chau Wu; Kin-chung Ho; Chin-cheung Tang; Yiu-hung Yau (Environmental Science and Pollution Research, 2021)

Meeting Report: N-Nitrosamine Impurity Control Strategies in the Pharmaceutical and Biotechnology Industries - Scott W. Roberts; Andrew Lennard; Ganapathy Mohan; James Bernstein; Nina S. Cauchon; Steve Cole; Noreen Curristin; Kim Huynh-Ba; Christine N. Kolz; Cheenu Murti; Kin Tang (The AAPS Journal, 2021)

Low-pass genome sequencing: a validated method in clinical cytogenetics - Matthew Hoi Kin Chau; Huilin Wang; Yunli Lai; Yanyan Zhang; Fuben Xu; Yanqing Tang; Yanfang Wang; Zihan Chen; Tak Yeung Leung; Jacqueline Pui Wah Chung; Yvonne K. Kwok; Shuk Ching Chong; et al. (Human Genetics, 2020)

Surface Dissolution UV Imaging for Investigation of Dissolution of Poorly Soluble Drugs and Their Amorphous Formulation - Chiau Ming Long; Kin Tang; Hitesh Chokshi; Nikoletta Fotaki (AAPS PharmSciTech, 2019)
The aim of this study is to investigate the dissolution properties of poorly soluble drugs from their pure form and their amorphous formulation under physiological relevant conditions for oral administration based on surface dissolution ultraviolet (UV) imaging. Dissolution of two poorly soluble drugs (cefuroxime axetil and itraconazole) and their amorphous formulations (Zinnat ® and Sporanox ® ) was studied with the Sirius Surface Dissolution Imager (SDI). Media simulating the fasted state conditions (compendial and biorelevant) with sequential media/flow rate change were used. The dissolution mechanism of cefuroxime axetil in simulated gastric fluid (SGF), fasted state simulated gastric fluid (FaSSGF) and simulated intestinal fluid (SIF) is predominantly swelling as opposed to the convective flow in fasted state simulated intestinal fluid (FaSSIF-V1), attributed to the effect of mixed micelles. For the itraconazole compact in biorelevant media, a clear upward diffusion of the dissolved itraconazole into the bulk buffer solution is observed. Dissolution of itraconazole from the Sporanox ® compact is affected by the polyethylene glycol (PEG) gelling layer and hydroxypropyl methylcellulose (HPMC) matrix, and a steady diffusional dissolution pattern is revealed. A visual representation and a quantitative assessment of dissolution properties of poorly soluble compounds and their amorphous formulation can be obtained with the use of surface dissolution imaging under in vivo relevant conditions.

‘One Health’ for the people of Hong Kong and the world - Kin-Hang Kok; Hei-Man Vincent Tang; Dong-Yan Jin (Science China Life Sciences, 2016)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

Immobilization of silver in polypropylene membrane for anti-biofouling performance - Xiaoying Zhu; Lin Tang; Kin-Ho Wee; Yong-Hong Zhao; Renbi Bai (Biofouling, 2011)